Jujuran Tradition In Banjar Marriages: Symbolic Deconstruction and Islamic Law Analysis (Asian Journal of Law and Humanity, 2026)
The practice of giving a wedding allowance (baantar jujuran) in traditional Banjar weddings often gives rise to ethical and economic tensions due to the high sums agreed upon amidst changing contemporary sociocultural conditions. This study provides an in-depth analysis of the sociological and symbolic meanings of the jujuran tradition among the Banjar community in Kandangan Kota Sub-district, South Hulu Sungai Regency, and examines its relevance to the principles of public interest in Islamic law. Using a qualitative research design with a cultural anthropological and Islamic law approach, data were collected through in-depth interviews with traditional leaders, local religious scholars, and married couples, and supplemented with documentation and community perception questionnaires. This study reveals that the Banjar community interprets jujuran not merely as an instrument of material transaction, but as a cultural symbolic system reflecting responsibility (amanah), respect (muru'ah), and the preservation of kinship harmony. However, in practical terms, a conceptual distortion occurs whereby jujuran is often equated with the dowry (sadaq), thereby creating a financial burden (israf) that contradicts the principle of ease in Islamic law. The tradition of jujuran can be categorised as 'urf shahih (a valid custom) in Islamic law provided that the amount is determined proportionally through consultation (syura) and does not negate the essence of the dowry as the wife’s absolute right. This study recommends a reorientation of customary policy towards the concept of Syarī‘ah al-‘Ādah to reconcile local cultural prestige with the universal public interest of Sharia..
Keywords: Jujuran Tradition; Banjar Marriage; 'Urf Shahih; Cultural Anthropology; Maqashid Syari'ah